1989
DOI: 10.1007/bf02365553
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal occurrence and abundance of caridean shrimp larvae at Helgoland, German Bight

Abstract: Plankton samples were collected from January 1985 to January 1986 three times per week at Helgoland to study seasonal occurrence and abundance of caridean shrimp larvae. A total of eleven species were obtained. Ninety-one % of all larvae collected during the sample period belonged to Crangon crangon L. and Crangon allmanni Kinahan, 6 % to Philocheras tn'spinosus Hailstone and3 % to the remaining eight species. Collections were generally dominated by C. placed into three different groups with respect to their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
(58 reference statements)
2
11
0
2
Order By: Relevance
“…The species composition is in general agreement with species encountered at Helgoland during an intensive one-year plankton samphng programme (Wehrtmann, 1989) (Table 3) ~ Z V" Fig. 11.…”
Section: Species Compositionsupporting
confidence: 77%
See 3 more Smart Citations
“…The species composition is in general agreement with species encountered at Helgoland during an intensive one-year plankton samphng programme (Wehrtmann, 1989) (Table 3) ~ Z V" Fig. 11.…”
Section: Species Compositionsupporting
confidence: 77%
“…However, larvae of T. cranchii were collected off Helgoland in 1990 and 1991 (Wehrtmann, in prep. ), and adult specimens of P. brevirostn's are relatively common near Helgoland (Wehrtmann, 1989). Furthermore, the distribution of the Palaemonidae clearly demonstrates that developmental stages of this family are confined to estuarine environments, and therefore they cannot be considered to be a regular component of the shrimp larval fauna at Helgoland.…”
Section: Species Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…At higher temperatures and planktonic food concentration, during late spring and summer (Wiltshire et al 2008), smaller shrimp larvae hatch in the southern North Sea. This match between favorable conditions of food availability and high temperatures with larval peak abundance during spring-summer (Wehrtmann 1989) allows the larvae to exploit rich food resources and reach fast rates of growth and development (Temming and Damm 2002). In this way, our study confirms the hypotheses proposed by Paschke et al (2004) and provides a chemical basis explaining the previously observed seasonal patterns in larval starvation resistance.…”
Section: Discussionmentioning
confidence: 99%